2D materials-based metal matrix composites. (29th July 2020) - Wen, Xinyue; Joshi, Rakesh
Abstract: 2D materials including graphene, transition metal dichalcogenide and hexagonal boron nitride (h-BN) have been widely incorporated with metal matrix to form 2D composites. These composites could be widely applied in the field of automotive, aerospace and marine technologies. Due to the strong covalent bonding and unique laminated structure of 2D materials, they can be used as structural reinforcement in metal matrix for enhanced mechanical and tribological properties. In this review, we first introduced various fabrication techniques for achieving high-reinforcement materials (graphene, MoS2, WS2 and h-BN) loading ratio and uniform distribution in the composites. Despite the availability of some conventional methods, we have also discussed novel approaches such as wet chemistry, hot extrusion and compression shearing for reducing contamination and minimizing energy consumption during the fabrication process. Examples of graphene-reinforced Al and Mg matrix composites are discussed where the graphene could effectively increase the tensile strength, compressive strength and hardness of the composites. We have also discussed the use of MoS2, WS2 and h-BN as self-lubrication additives in Al and Cu matrix to reduce the friction coefficient and wear rate.